Towards an Uthmanic Model of Quranic Orthography in Braille - Zarif, MMM; Usman, AQU; Jaafar, N (Univ Sultan Azlan Shah, 2024)
The adaptation of Braille in writing the Quran is one of the most important contributions of the Muslims to ensure that the visually challenged amongst them are able to learn and read the words of God. To date, Muslim countries, including Malaysia, have produced their own versions of the Quran in Braille, yet these Qurans are not based on the Uthmanic method of Quranic orthography. Consequently, this has led to variations, mistakes and inconsistencies in the spelling and marking of the Quranic verses. In this paper, the aim is to propose an Uthmanic model of Quranic orthography in Braille. It focuses on the chapter of Maryam as its sample and applies the qualitative methods of textual and comparative analysis on the revelational criteria of Quranic orthography and the limitations of the Braille writing system. This results in a more standardized and adaptable model of Quranic orthography in Braille with minimal changes in the use of vocalization and other diacritical marks of the Quran. Currently, this model is proposed to serve as a basis for the development of a national standard of Quranic orthography in Braille by the relevant authorities in cooperation with the visually challenged organizations in Malaysia.